Panduan Kunjungan ke Rumah Ibadat Bukan Islam oleh Masyarakat Muslim di Malaysia: Tinjauan Perspektif Akidah-Perbandingan Agama, Fiqh dan Undang-Undang: Guidelines for Muslim Visits to Non-Muslim Places of Worship in Malaysia: A Review from the Perspectives of ʿAqīdah - Comparative Religion, Fiqh and Law - Mohd Khambali @ Hambali, Khadijah; Abdul Khalil, Shahidra; Daud, Mohd Zaidi; Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This paper examines the issue of Muslim visits to non-Muslim places of worship within the context of Malaysia’s pluralistic society. While the academic discipline of Comparative Religion plays a significant role in promoting interfaith understanding, the implementation of such visits must be carefully scrutinized from various angles, including Islamic creed (ʿaqīdah), religious study, jurisprudence (fiqh), legal considerations and local cultural sensitivities. The paper underscores the importance of applying the principle of sadd al-dharā’iʿ (blocking the means to potential harm) to avoid doctrinal confusion and the risk of tashabbuh (imitation of non-Islamic religious rituals), especially when the visits involve members of the public or students who may lack adequate guidance. In this regard, the presence of qualified experts in ʿaqīdah, fiqh, and Comparative Religion is essential to ensure that Islamic legal boundaries are respected and that the intended message of harmony is conveyed accurately. Furthermore, the paper proposes clear guidelines for visits to churches, Hindu temples, Buddhist and Taoist temples and gurdwaras, as a preliminary step towards more cautious and structured implementation. It concludes by urging state religious authorities to take proactive measures by initiating dialogues with relevant stakeholders to develop a comprehensive framework that preserves the integrity of Islamic belief while fostering interfaith understanding and coexistence in Malaysia.